Alfonso Lacadena García-Gallo (1964-2018): "curriculum vitae" - Lacadena García-Gallo, Alfonso (Revista Española de Antropología Americana, 2019)
Alfonso Lacadena García-Gallo (1964-2018): "curriculum vitae"